“The Once Bright City Became Gloomy and Sad:” Survivor of 2014 Odessa Massacre Reflects Back on Tragedy - CovertAction Magazine - Kuzmarov, Jeremy (2022)
Massacre part of planned act of intimidation by U.S.-installed government and precipitated civil war in Ukraine On May 2, 2014, at least 48 people were killed when right-wing Ukrainian forces burned down the Trade Unions Building in Odessa. The victims had taken refuge in the building after opposing the February 2014 coup d’etat in Ukraine